Pengaruh ATM, BOPO, NPL, LDR, dan ESG terhadap Profitablitias Bank Umum di Indonesia - Jefry Jefry; Foza Hadyu Hasanatina (Diponegoro Journal of Management, 2026)
This study aims to examine the relationship between Automated Teller Machines (ATMs), Break Even Point of Operating Expenses to Operating Income (BOPO), Non-Performing Loan (NPL), Loan-to-Deposit Ratio (LDR), and Environmental, Social, and Governance (ESG) considerations with Return on Assets (ROA). Using a sample of companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024, the sample was selected through purposive sampling, comprising a total of 25 companies meeting specific criteria. The analytical approach employed was panel data regression analysis, with the Fixed Effects Model used as the preferred method to directly assess the relationships between independent variables and ROA. The findings indicate that ATMs have an insignificant negative relationship with ROA. Conversely, BOPO, NPLs, and LDR exhibit significant negative relationships with ROA. ESG demonstrates a positive, albeit insignificant, relationship with ROA. Overall, a significant association was observed between these variables and ROA.